Assessing Service Quality in Passport Application Mobile Apps(M-Paspor) and its Influence on User Satisfaction: A Case Study using e-GovQual - Yaziji, Warda; Aprilia, Relaci; Sensuse, Dana Indra; Lusa, Sofian; Wibowo, Prasetyo Adi (The Indonesian Journal of Computer Science, 2023)
Technological advances in this era can support public services to serve the public more quickly and responsively. One of the electronic public services used by citizens in Indonesia is the application for a passport. After launching to the public in early 2022, the mobile app M-Paspor is still experiencing some obstacles. This study aims to get recommendations for government consideration based on public experience as users of the M-Paspor application. This study integrates the e-Govqual model initiated by Papadomichelaki & Mentzas and End User Computing Satisfaction by Doll & Tork Zadeh. Six dimensions are used: ease of use, trust, functionality of the interaction environment, reliability, content and appearance of information, and citizen support. With the questionnaire distributed through social media, we analyzed data from 111 respondents. We conducted an analysis using SmartPLS to validate the survey. The result implied that Citizen Support, Functionality of the Interaction Environment, and Reliability significantly influence End User Computing Satisfaction of M-Paspor users